Identifying the potential visual elements and handicrafts for food packaging (a case study of Melaka SMEs) / Wan Nurul Izzati Wan Muhammad Zulkifli - Wan Muhammad Zulkifli, Wan Nurul Izzati (2015)
Traditionally, packaging is limited to something that protects the product content from any physical obstacle and safe methods. From years to years packaging continues to grow and evolve as external elements of the product that encompassing the physical appearance. Towards issues regarding packaging design in Malaysia, a lot of efforts were taken by the Malaysian government to improve the quality of packaging design particularly for SME’s product. Across this effort, a few claims were still established in regards of packaging design weakness. Moreover, through pilot study that has been conducted, it is defined that the existing SME’s food in Melaka are still not having a good appearance in terms of design and quality material. Thus, based on that, a study was conducted by taking SME’s food packaging in Melaka as a case study. The aims is to improve the low quality existing packaging design of Melaka SME’s food product by establishing the potential visual elements of packaging design and potential handicraft that can be used as a future material. Throughout the case study, two different methods were used: a contextual document analysis and a face to face interview. The results revealed that color, material and graphics are the potential visual elements that should be used by the designers in the future for designing Melaka SME’s food packaging. The study also established four empirical reason from the design perspective in explaining the failure of the existing Melaka SME’s food packaging and providing a new proposed guideline in terms of effective’s visual elements for Melaka SME’s food packaging and natural-based material that originated from Melaka is the best material and concept that can be using as an appropriate material in future.